IMPLEMENTASI MODEL ASSURE BERBASIS VIDEO YOUTUBE DALAM MENINGKATKAN PEMAHAMAN MATERI FATHU MAKKAH DI TPA AL-FITRAH YOGYAKARTA - Fatur Rahman; Fahmi Makraja; Mohammad Riefyal Moulana (Fakultas Tarbiyah IAI Almuslim Aceh, 2025)
This study aims to describe and analyze the implementation of the YouTube video-based ASSURE model in improving students' understanding of Fathu Makkah material at TPA Al-Fitrah. The method used is descriptive analytical with a qualitative approach. Data were collected through observation, interviews, documentation, and learning outcome tests. The results showed that the application of the ASSURE model consisting of six stages (Analyze Learners, State Objectives, Select Methods, Utilize Media, Require Learner Participation, and Evaluate and Revise) was successfully implemented systematically. The YouTube video media used contains Islamic history narratives with interesting visualizations and a duration of 7-10 minutes, proven to be able to increase students' interest in learning and understanding. The average pre-test score of 45% increased to 82% in the post-test. Observations and interviews showed an increase in participation and enthusiasm for learning. Technical constraints such as device and connection limitations are overcome through adaptive strategies. The conclusion of this study is that the YouTube video-based ASSURE model is effective as an alternative to learning Islamic history in the TPA environment, and is able to significantly improve understanding of the material.